Three case reports of West Nile virus neuroinvasive disease: lessons from real-life clinical practice - Camilla Falcinella; Marina Allegrini; Lidia Gazzola; Giovanni Mulè; Daniele Tomasoni; Ottavia Viganò; Antonella d’Arminio Monforte; Giulia Marchetti; Camilla Tincati (BMC Infectious Diseases, 2021)
Abstract Background Despite being an uncommon cause of meningoencephalitis, West Nile virus (WNV) recently provoked significant outbreaks throughout Europe. West Nile neuroinvasive disease (WNND) is associated with significant morbidity and mortality in older and compromised individuals, while its diagnosis may be demanding for the clinician. Here discussed are three cases of WNND with a focus on the diagnostic challenges they presented due to atypical clinical presentation and laboratory findings. Case presentation Between July and September 2020 three patients presented to our attention with signs and symptoms compatible with meningoencephalitis. Among routine procedures, they underwent lumbar puncture and imaging. In the absence of microbiological isolates, biological samples were sent for serology and NAATs for WNV. Following diagnosis, the patients gradually recovered and were discharged either home or to rehabilitation facilities. Conclusions The laboratory findings here discussed, in particular CSF parameters, are only partially consistent with those described in the literature, which highlights the need for further research. While serology and NAATs on blood and urine appear the most reliable techniques in the diagnostic work-up of WNND, utility of NAATs on CSF specimens is limited by the kinetics of WNV viremia in biological fluids. This report underlines that WNND should always be included in the differential diagnosis of meningoencephalitis during WNV transmission period.